Comparative analysis of transcriptional changes in zebrafish cep290 and bbs2 mutants by RNA-seq reveals upregulation of inflammatory and stress-related pathways - Grabinski, Sarah E.; Parsana, Dhwani; Perkins, Brian D. (Frontiers in Molecular Neuroscience, 2023)
Acute injury to the adult zebrafish retina triggers the release of pro-inflammatory cytokines and growth factors that stimulate multiple gene regulatory networks, which ultimately stimulate Muller glia to proliferate and regenerate neurons. In contrast, zebrafish carrying mutations in cep290 or bbs2 undergo progressive loss of cone photoreceptors and exhibit signs of microglia activation and inflammation, but the mutants fail to stimulate a regeneration response. To identify transcriptional changes that occur in zebrafish mutants undergoing progressive photoreceptor degeneration, RNA-seq transcriptional profiling was performed on cep290-/- and bbs2-/- retinas. The PANTHER Classification System was used to identify biological processes and signaling pathways that were differentially expressed between mutants and wild-type siblings during degeneration. As expected, genes associated with phototransduction were downregulated in cep290 and bbs2 mutants compared to wild-type siblings. Although both cep290 and bbs2 mutants undergo proliferation of rod precursors in response to retinal degeneration, the process of negatively regulating proliferation is enriched for upregulated genes, and this negative regulation may restrict proliferation of Muller glia and inhibit regeneration. A total of 815 differentially expressed genes (DEGs) were shared by cep290 and bbs2 retinas. Genes in pathways associated with inflammation, apoptosis, stress response, and PDGF signaling were overrepresented. Identifying the genes and biological pathways that are common in zebrafish models of inherited retinal degeneration provides a foundation for future studies on the mechanisms that regulate cell death as well as processes that prohibit Muller cell reprogramming or proliferation in a model capable of retinal regeneration. The pathways will provide targets for future interventions that may promote successful regeneration of lost photoreceptors.